Quality of life of a person with Parkinson's disease and the relationship between the time of evolution and the severity of the disease Calidad de vida de las personas con enfermedad de Parkinson y su relación con la evolución en el tiempo y la gravedad de la enfermedad Qualidade de vida de indivíduos com Parkinson e sua relação com tempo de evolução e gravidade da doença - Fabiana Magalhães Navarro-Peternella; Sonia Silva Marcon (Universidade de São Paulo, 2012)
Parkinson's disease can cause disability and decrease the quality of life in its sufferers. The aim of this study was to evaluate the quality of life of a group of people with Parkinson's disease and whether a relationship exists between time of evolution and severity of the disease. Secondary analysis was carried out on transversal data collected from 40 individuals with Parkinson's disease registered in the Parkinson's Association of Maringá, in Maringá-PR-Brazil. Measures: three instruments were applied: a socio-demographic questionnaire, the Hoenh and Yahr Scale and the Parkinson's Disease Questionnaire (PDQ-39). According to PDQ-39, men referred to a lower quality of life, although, statistically, there was no significant difference between the two genders. Differences were only observed in the dimensions of "activities of daily living" and "social support", in which men presented higher impairment, and "emotions" and "bodily discomfort", where women showed higher impairment. Furthermore, severity of disease tended to lead to a perception of lower quality of life regarding the dimensions of "activities of daily living" and "cognition", which is relevant to improve clinical guidance and intervention. La enfermedad de Parkinson puede llegar a ser incapacitante y afectar a la calidad de vida de los pacientes. El objetivo de este estudio fue evaluar la calidad de vida de las personas con Parkinson e identificar las relaciones con el transcurso del tiempo y la gravedad de la enfermedad. Los datos fueron recogidos en la ciudad de Maringá-PR-Brasil, con 40 personas indexadas en la "Associação Maringaense de Parkinson", a través de la aplicación de tres instrumentos: cuestionario sociodemográfico, escala de Hoenh e Yahr y PDQ-39. De acuerdo con el PDQ-39, los hombres reportaron peor calidad de vida, aunque no hubo diferencias estadísticas entre los sexos. Las diferencias apenas se observaron en la dimensión "actividades de vida diaria" y "apoyo social", con los hombres presentando una mayor participación y "bienestar emocional" e "incomodidad física" con una más grave entre las mujeres. Por otra parte, la gravedad de la enfermedad mostró una tendencia a empeorar la percepción en la calidad de vida en las dimensiones de las actividades de la vida diaria y cognición, puntos importantes para una mejor orientación e intervención clínica. A doença de Parkinson pode ser incapacitante e prejudicar a qualidade de vida de seus portadores. O objetivo do estudo foi avaliar a qualidade de vida de indivíduos com Parkinson e identificar relações com o tempo de evolução e gravidade da doença. Os dados foram coletados na cidade de Maringá, PR, Brasil, com 40 indivíduos cadastrados na Associação Maringaense de Parkinson, por meio da aplicação de três instrumentos: questionário sociodemográfico, escala de Hoenh e Yahr e PDQ-39. De acordo com o PDQ-39, os homens referiram pior qualidade de vida, embora sem diferenças estatísticas entre os sexos. Diferenças foram observadas apenas na dimensão "atividades de vida diária" e "apoio social", com os homens apresentando maior acometimento e "bem-estar emocional" e "desconforto corporal", com maior comprometimento entre as mulheres. Por outro lado, a gravidade da doença apresentou tendência a pior percepção na qualidade de vida nas dimensões atividades de vida diária e cognição, pontos relevantes para melhor orientação clínica e intervenção.